Automatic Cat Flap / Nurdiyana Muhammad Zaidi, Juliane Senik @ Nawi and Mohamad Afiq Mohd Rosdi - Muhammad Zaidi, Nurdiyana; Senik @ Nawi, Juliane; Mohd Rosdi, Mohamad Afiq (2013)
Automatic Cat Flap is one of the projects that can help our pets to enter and exit the house safely and quick as it can without human assistant. Based on the observation, people had some problem when manage their pets. For example their pets were threatening by others animal and could be danger the pet it selves. The system of the Automatic Cat Flap is to detect the magnet at the cat’s collar with sensing coil. When the cats enter through the flap, the solenoid will release it shaft and the flap opened automatically for several second. It will lock back and reed switch gives an alert to the household with the melody sound. This system was similar when the cats exit from the flap. We used 2 IC which is CA3130A on the cat flap circuit and M 3485 on the melody circuit. This project used 12V and ,9V supply to operate the cat flap circuit. While at the melody circuit we used 3 V supply to operate.